DEVELOPMENT OF TECHNOLOGY FOR SINGLE -OPERATION CUTTING OF NONFERROUS METAL SHEETS - Tarasov , Vyacheslav; Potapenkov , Alexander; Rumyantsev , Vladislav; Kuris , Yurij; Mosejko , Yurij (Scientific Journal "Metallurgy", 2020)
To improve the efficiency of small cutting plates consist of a critical analysis of the known technologies and devices. Modern plasma-arc cutting technology of the plates allows the processing of conducting metals and dielectrics without overheating zone of the section and the structure violation. However, too thin and thick sheets deteriorates the overall straightness of cutting. The use of this technology is appropriate for manufacturers of mass production and cutting unprofitable for small series and vary orders. Laser cutting technology is not inferior to the processing accuracy of the plasma. However, this technology requires additional heating of staff, careful observance of specified quality of material, purity of gas, the condition of the nozzles. Disadvantages: ribbed surface area of the cut, the higher the cost of production. More simple and cheap seems to be hydro abrasive cutting. Despite the universality, the technology requires expensive and sophisticated equipment and additional processing cutting products in compliance with regulatory environmental requirements. In this regard, it seems appropriate to develop and improve the technology of small mechanical cutting of plates of non-ferrous metals, including Nickel cathode. For the basic framework adopted technology two operational cutting: first cutting the sheets into strips, and then cutting is carried out on a rectangular plate of small dimensions. The main problem is the curvature of the headquarters of Nickel after the first operation of cutting the sheets. There is a need for additional leveling before the subsequent manufacturing of small plates the right size. To remove these shortcomings, developed advanced technology and device for operating one cutting, which includes a separate cutting mechanism and the boot device. The technology for such cutting was tested on a laboratory bench. The analytical study of cutting parameters and developed a physical model of one of the operating technology. Produced pilot cutting device that provides the cathodic Nickel plates 50x50 mm, sheet thickness up to 10.0 mm. Developed a special cutting device automatic action, which allows significantly simplify the technology of cutting sheets and improve the production efficiency of small plates.